Assessing the Immunomodulatory Activity of Ethanol Extract of Sambucus javanica Berries and Leaves in Chloramphenicol-Induced Aplastic Anemia Mouse Model - Wira Eka Putra,; Muhaimin Rifa’i, (Tropical Life Sciences Research, 2020)
Aplastic anemia, life-threatened disease, is a hematologic disorder characterised by bone marrow hypoplasia. Multiple modalities such as bone marrow transplantation and immunosuppression treatment have been proposed to ameliorate this entity, however it remains ineffective. Sambucus, a group of herb plants, possesses a broad spectrum of medicinal properties such as antioxidant, insulin-like activity, anticancer and antiviral. However, the study about its activity toward aplastic anemia incidence is based on limited data. Thus, the research aim of this study was to evaluate the immunomodulatory activities of Sambucus javanica in chloramphenicol-induced anemia aplastic mouse model. In this present study, BALB/c mice were administrated with chloramphenicol (CMP) to induce aplastic anemia then followed by S. javanica extracts treatment. Additionally, cellular and molecular aspects were evaluated by flow cytometry and Hematoxylin-Eosin staining. Further analysis showed that S. javanica extracts could promote the population number of regulatory T-cells and naïve cytotoxic T-cells. Moreover, those extract also reduced the inflammation and necrotic incidence in CMP-induced mouse aplastic anemia model. Together, these results suggest that S. javanica has therapeutically effect to aplastic anemia by altering the immune system as an immunomodulatory agent.